6th International Conference EnRe - Energy & Responsibility: Book of Extended Abstracts (University of Maribor Press, 2024)
In the context of escalating climate challenges, the EnRe conference is dedicated to exploring pathways to climate neutrality and the sustainable green transition. The conference is focused on the development and implementation of innovations supporting the transformation of energy systems, industrial systems, and living systems, all with the goal of creating a sustainable future with net-zero emissions. The conference brings together experts, researchers, policymakers, and business leaders to share their experiences, research, and visions. The aim of the conference is to foster collaboration and exchange of ideas, and to collectively develop comprehensive approaches and strategies for achieving climate neutrality. This conference is not just a knowledge exchange, but also a platform for encouraging concrete actions that will ensure a greenerand more sustainable future for our next generations to come.